Analisis Manajemen Pelayanan Rumah Sakit Terhadap Kualitas Pelayanan Publik Pada RSUD Panglima Sebaya Paser - Nurnaningsih, Nurnaningsih (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
Hospitals are expected to be able to provide quality health services, so that people can live healthily and achieve the goal of equitable health development. There are three parties involved in health services at hospitals, namely the providers and service providers and the service users. The aim of this research is to determine the form of service management carried out by the Regional General Hospital Panglima Sebaya on the quality of public services in Paser Regency. This research is descriptive qualitative in nature using observation and interview methods with a sample of 30 people, consisting of doctors, nurses, administrative officers and outpatients. This research shows that the quality of service at Regional General Hospital Panglima Sebaya is seen based on Reliability, Responsiveness, Tangibility, Assurance and Empathy which have been fulfilled properly while the service system that is owned has fulfilled the principles of simplicity and clarity. Management of health service quality at Panglima Sebaya Hospital was generally considered good